2022
DOI: 10.52812/msbd.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automotive Parts Suppliers through Ordinal Priority Approach and TOPSIS

Abstract: The problem of supplier selection is an important concern for all businesses. Also, as environmental concerns are mounting and socio-economic crises are increasing worldwide, the need for resilient and environment-friendly suppliers is aggravating. Companies are under tremendous pressure to redefine their business practices and operations to achieve sustainability goals while being resilient. The study aims to evaluate the Chinese automotive parts suppliers based on 'gresilience' (green and resilient) criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Since the last few years, the researchers have endeavoured to explore its capability in solving diverse MCDM problems, like selection of healthcare supplier (Quartey-Papafio et al ., 2021), construction sub-contractor (Mahmoudi and Javed, 2022), project portfolio (Mahmoudi et al ., 2022a), transportation planning strategy (Pamucar et al ., 2022), road maintenance strategy (Bouraima et al ., 2022), distributed ledger technology (Sadeghi et al ., 2022a) and so on. Recently, it has also been successfully combined with TOPSIS for project selection (Mahmoudi et al ., 2021a), and shortlising of automotive parts suppliers (Bah and Tulkinov, 2022); data envelopment analysis (DEA) for supplier performance assessment (Mahmoudi et al ., 2022b); FST for selection of resilient suppliers selection (Mahmoudi et al ., 2022c), blockchain technology selection in construction organizations (Sadeghi et al ., 2022b) and appraising construction suppliers (Mahmoudi et al ., 2022d); neutrosophic fuzzy set for industrial robot selection (Abdel-Basset et al ., 2022); rough set theory for sustainable mining (Deveci et al ., 2022); and grey system theory to evaluate low-carbon sustainable technologies in agriculture (Shajedul, 2021), sustainable supplier selection for construction megaprojects (Mahmoudi et al ., 2021b) and identification of barriers to electric vehicle adoption (Candra, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last few years, the researchers have endeavoured to explore its capability in solving diverse MCDM problems, like selection of healthcare supplier (Quartey-Papafio et al ., 2021), construction sub-contractor (Mahmoudi and Javed, 2022), project portfolio (Mahmoudi et al ., 2022a), transportation planning strategy (Pamucar et al ., 2022), road maintenance strategy (Bouraima et al ., 2022), distributed ledger technology (Sadeghi et al ., 2022a) and so on. Recently, it has also been successfully combined with TOPSIS for project selection (Mahmoudi et al ., 2021a), and shortlising of automotive parts suppliers (Bah and Tulkinov, 2022); data envelopment analysis (DEA) for supplier performance assessment (Mahmoudi et al ., 2022b); FST for selection of resilient suppliers selection (Mahmoudi et al ., 2022c), blockchain technology selection in construction organizations (Sadeghi et al ., 2022b) and appraising construction suppliers (Mahmoudi et al ., 2022d); neutrosophic fuzzy set for industrial robot selection (Abdel-Basset et al ., 2022); rough set theory for sustainable mining (Deveci et al ., 2022); and grey system theory to evaluate low-carbon sustainable technologies in agriculture (Shajedul, 2021), sustainable supplier selection for construction megaprojects (Mahmoudi et al ., 2021b) and identification of barriers to electric vehicle adoption (Candra, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has also been successfully combined with TOPSIS for project selection (Mahmoudi et al, 2021a), and shortlising of automotive parts suppliers (Bah and Tulkinov, 2022); data envelopment analysis (DEA) for supplier performance assessment (Mahmoudi et al, 2022b); FST for selection of resilient suppliers selection (Mahmoudi et al, 2022c), blockchain technology selection in construction organizations (Sadeghi et al, 2022b) and appraising construction suppliers (Mahmoudi et al, 2022d); neutrosophic fuzzy set for industrial robot selection (Abdel-Basset et al, 2022); rough set theory for sustainable mining (Deveci et al, 2022); and grey system theory to evaluate low-carbon sustainable technologies in agriculture (Shajedul, 2021), sustainable supplier selection for construction megaprojects (Mahmoudi et al, 2021b) and identification of barriers to electric vehicle adoption (Candra, 2022).…”
Section: Opamentioning
confidence: 99%
“…Mahmoudi and Javed (2022b) used the OPA to evaluate Iranian construction sub-contractors. Bah and Tulkinov (2022) used the OPA to rank the automotive parts suppliers. Mahmoudi et al (2021c) showed the feasibility of the OPA for handling big data.…”
Section: Grey Ordinal Priority Approachmentioning
confidence: 99%
“…The findings show that digitization and on-site renewable energy are the most crucial industrial recovery solutions. OPA and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methodologies were used by Bah and Tulkinov (2022) to assess Chinese suppliers of automotive components using resilience criteria. However, there is no existing study until now that applied the OPA approach in the road sector, especially the factors affecting its maintenance.…”
Section: Introductionmentioning
confidence: 99%